Internalisasi Pendidikan Agama Islam Melalui Budaya Religius dalam Menanggulangi Penyalahgunaan Narkoba di MAN Tuban - Ahmad Syaifudin (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2018)
The big question that appear in the midst of mankind today is the dryness of the spiritual aspect. This study departs from a concern and at the same expectations. Why in this era of globalization has increased the problem of moral decadence , so parents are increasingly concerned about the negatives of globalization , ie the easy moral values ​​which negatively affects proteges primarily occurring drug abuse among students. Therefore internaliasi PAI through religious culture considered very necessary to be implemented in suppressing the abuse that occurred in MAN Tuban . The purpose of this study are ( 1 ) Describe the application of religious culture in MAN Tuban . ( 2) to identify factors that cause drug abuse in Tuban MAN . ( 3 ) Explores Internalization of Islamic education through religious culture in tackling drug using in MAN Tuban . This study is a qualitative research with a sociological approach . While the specification of this research using descriptive method that is as problem-solving procedures are investigated , by describing / depicting the state of the object of research at the present time , based on the facts that appear or as it is. From this research resulted in several findings : (1 ) Application of Religious Culture in MAN Tuban carried out in several ways , namely the creation of a religious atmosphere , the internalization of religion , ideals , habituation , forming attitudes and behavior . ( 2 ) Some of the causes of drug abuse in MAN Tuban is the basis of religion is not strong , two-way communication between parents and children is very rare, the effect of living environment, a culture that goes through the electronic and the print media . ( 3 ) the internalization of Islamic education through religious culture in tackling drug abuse implemented with emphasis on programs related to religious culture in MAN Tuban is through the provision of knowledge theoretically , through religious activities conduc ted by Extracurricular at MAN Tuban , through the establishment MAN religious culture in Tuban , through integration with a wide range of science. Keywords : internalization , Islamic religious education , religious culture , drug abuse